Factors Influencing Patient Satisfaction in Shahroud Hospitals in 2018 - Amiri 1, Mohammad; Sadeghi 2, Elham; Khosravi 3*, Ahmad (Shahroud Journal of Medical Sciences, 2019)
Background: Patient satisfaction is one of important indicators of quality of service measurement. This study aimed at measuring patient satisfaction and factors which influence it in hospitals in Shahroud.Methods: In this cross-sectional study, 800 patients selected through random sampling were studied in public and private hospitals in 2018. The collected data were entered into SPSS 16 and analyzed using t-test and chi-square. The level of significance in all tests is 0.05.Results: Most of the inpatients were women and married people. The average score of satisfaction in the public hospitals affiliated to the University was 22.45 ± 6.02 and in the private sector, it was 21.56 ± 5, which is deemed moderate. Patients were the most dissatisfied with the daily change of patient dresses and bed covers (38.3%), hospital food quality (35.3%), room facilities (31.1%), and were the most satisfied with nursing behaviors (87.7%). Chi-square test showed a significant relationship between the type of hospital (P = 0.002), patients’ age (P = 0.037), education (P = 0.013), and residence (P = 0.012) with their satisfaction.Conclusion: Patients' satisfaction was moderate. Paying more attention to the domains such as daily change of clothes and bed covers, the quality of hospital food, and facilities of the patient's room can play a role in improving the satisfaction of patients.